FORCE MAJEURE (OVERMACHT) DALAM HUKUM KONTRAK (PERJANJIAN) INDONESIA - Isradjuningtias, Agri Chairunisa (Faculty of Law, Parahyangan Catholic University, 2015)
AbstractPrivate law in civil law system is generally contains two major sections: contract law and commercial law. In contract law, parties imposed upon themselves certain obligations. Notwithstanding that, parties may at some point lose their ability to meet their obligations due to overmacht/force majeure. This article examine the legal status force majeure in Indonesia contract law. Force Majeure is intended to protect one party from damage arising from non- performance. The existence of which require the fulfillment of one or two conditions, subjective and objective. The Force Majeure clause is regulated in the Civil Law Code and encompasses situations such as fire, flood, earthquake, strom, typhoon (or other natural disaster), loss of electricity, catalisator damage, sabotage, war, invasion, civil war, rebellion, revolution, military coup, terrorist activities, blockade, embargo, labour dispute, strike, and goverment sanctions.